2008
DOI: 10.1186/1471-2180-8-198
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality and outbreak of a predominant Streptococcus pneumoniae serotype 1 clone from The Gambia: Expansion of ST217 hypervirulent clonal complex in West Africa

Abstract: Background: Streptococcus pneumoniae serotype 1 causes > 20% of invasive disease, among all age groups combined, in The Gambia. In contrast, it is rarely detected in carriage studies. This study compares the molecular epidemiology of S. pneumoniae serotype 1 causing invasive disease in The Gambia between 1996 and 2005 to those carried in the nasopharynx between 2004 and 2006.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 16 publications
(37 reference statements)
5
65
1
Order By: Relevance
“…Interestingly, the observed higher resistance to tetracycline was much higher than to chloramphenicol in the West African lineage despite the presence of only Tn 5253 element which carries resistance conferring genes for both antibiotics [76]. This observation was consistent with previous study from the Gambia, which also reported such a discrepancy using in vitro phenotypic data [77]. Because resistance to both antibiotics was due to the presence of only the Tn 5253 element, this suggested that the chloramphenicol resistant isolates contained a deletion of the chloramphenicol resistance encoding loci.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Interestingly, the observed higher resistance to tetracycline was much higher than to chloramphenicol in the West African lineage despite the presence of only Tn 5253 element which carries resistance conferring genes for both antibiotics [76]. This observation was consistent with previous study from the Gambia, which also reported such a discrepancy using in vitro phenotypic data [77]. Because resistance to both antibiotics was due to the presence of only the Tn 5253 element, this suggested that the chloramphenicol resistant isolates contained a deletion of the chloramphenicol resistance encoding loci.…”
Section: Discussionsupporting
confidence: 88%
“…This further suggests that the deletion of the chloramphenicol resistance encoding loci was restricted to the West African isolates. These findings explain why ST217 isolates from West Africa are more susceptible to chloramphenicol than tetracycline as previously reported [77]. …”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Of note, 88.3% (95% CI 43.2, 99.6) and 98.6% (95% CI 70.6, 100.0) of serotypes causing nonbacteremic pneumonia and noninvasive disease were included in the available PCV10 and PCV13, respectively (Appendix Figure 1). Serotypes 1 and 5, which are the most commonly identified serotypes in previous studies in Africa 4649 and in more recent outbreaks, 50,51 accounted for 12.8% (95% CI 4.9, 24.0) of meningitis, 10.2% (95% 5.7, 15.6) of IPD, and 6.1% (95% CI 0.0, 71.2) of nonbacteremic pneumonia/noninvasive cases, respectively.…”
Section: Resultsmentioning
confidence: 75%
“…Genetically, the lineage occurring in Bangladesh is distinct from the historic strain D39 isolated in the early 1900 s.The meningitis-causing feature of the serotype-2 pneumococcal lineage reported here is unusual or even unparalleled for a pneumococcus in having such a high odds for causing meningitis. In studies of meningitis from Africa, compared to serotype-1, serotype 2 did not account for a prominent proportion of meningitis cases [18], [19], [20]. It raises the question of whether a variant with specific central nervous system tropism has recently evolved within the clonal complex CC74 in Bangladesh which differentiates it from the members of the same lineage observed in West Africa [11].…”
Section: Discussionmentioning
confidence: 99%